MEMORY INSTITUTIONS: DEPOSITORIES, THEATRES, TREASURIES OR DATA BASES? - MANŽUCH, ZINAIDA (Knygotyra, 2015)
Archives, museums and libraries appeared in the whirl of changes inspired by the introduction of new communication technology which initiated transition from print to digital culture. The time of change is the time of creating future visions and scenarios of archives, museums and libraries. These institutions are frequently called „memory institutions“ in order to higlight their common roles in communicating memory. Often speculations and metaphors of memory institutions (e.g. library/archive as computer, digital repositories etc.) lack clear understanding of what memory is. Therefore, the main objective of this article is to define and evaluate paradigms of memory communication, which determine strategies of cultural heritage dissemination in the contemporary archives, museums and libraries, and assess both their roots and future perspectives. For this purpose current knowledge about communication of memory in archival science, museology and library science is summarised; major principles of memory communication in archives, libraries and museums are generalised, Abstractbasing on the theories of memory; and current paradigms of memory communication as well as their development are analysed, relying on the ars memoriae research. Two paradigms of memory communication have been distinguished: memory-as-computer and memory-as-theater. It is concluded that communication of memory requires integration of two dimensions: 1) social, which covers contextualisation of cultural heritage resources with reference to present needs of societies and 2) narrative, which refers to meaningful structures that transform heritage objects into meaningful stories of the past. It is concluded that memory-as-computer paradigm neglects the necessity of heritage contextualization and interpretation because it relies on the statement that there is a universal code for representation and management of any information. With increasing volumes of cultural heritage available online these collections may become meaningless to users. The paradigm of memory-as-theater demonstrates an increased interest to the new ways of interaction between users and heritage objects in the digital environment; however, the same as the first paradigm it ignores social objectives and context for communication of memory. In this light, the third paradigm, providing an integral approach to all dimensions of memory communication should be developed.